Bullous pemphigoid and its association with neurological diseases - Charl P. Smit; Nicola A. Gray; Willem I. Visser (Journal of the Colleges of Medicine of South Africa)
Background: Bullous Pemphigoid (BP) is the most common immunobullous skin disease.